Why Did Prophet Muhammad Sallallahu Alayhi Wa Sallam Marry Hazrat Zaynab Bint Jahsh Who was His Cousin and Stepson’s and Adopted Son’s Wife? - Guru Dev Teeluckdharry (Penerbit Hellow Pustaka, 2025)
According to many Jewish, Christian, and Hindu opponents of Islam, Prophet Muhammad Sallallahu Alayhi Wa Sallam (The Last and Final Prophet of Islam - Peace Be Upon Him) was a sexual pervert and incestuous father-in-law because he married his cousin and adopted son’s wife called Hazrat Zaynab bint Jahsh (ra). Many Muslim Scholars, Ulemas, Mawlanas, and Clerics have refuted such a blasphemous allegation through the statement that the marriage of Hazrat Zaynab bint Jahsh (ra) with Prophet Muhammad Sallallahu Alayhi Wa Sallam (The Last and Final Prophet of Islam - Peace Be Upon Him) occurred due to a Divine Revelation from ALLAH, The Most Merciful and Most Gracious as stipulated in Surah Al-Ahzab 33:37, 33:38, and 33:39 of The Glorious Quran.